Determinan Yang Memengaruhi Pemilihan Saluran Pemasaran Kopi Robusta Di Kabupaten Malang - Noviyanti, Annisa; Nurmalina, Rita; Dwi Utami, Anisa (Magister Science of Agribusiness, Department of Agribusiness, FEM-IPB University, 2024)
ABSTRACT The demand for coffee in Malang Regency by determining the quantity of commodities is very dependent on the marketing subsystem. Robusta coffee marketing channels in Malang Regency include marketing institutions, namely small traders, sub-district collectors and large traders. Coffee marketing is dominated by small traders. This research aims to analyze the determinants that influence the choice of marketing channels for Robusta coffee in Malang Regency. The location of this research was carried out in two villages, namely Srimulyo Village and Sukodono Village, Kec. Dampit, Kab. Poor. The respondents in this research were Robusta coffee farmers in two villages in a total of 60 respondents. Marketing agency respondents were then determined using snowball sampling techniques. Snowball sampling method by collecting data based on information from previous respondents based on existing marketing patterns in Malang Regency. This research uses multinomial logit analysis by determining efficient marketing channels as a reference variable. Based on the results of marketing channel analysis, it was found that there are 5 marketing channel patterns. Marketing channel 1 consists of 27 farmers and the largest channel choice is 45%, while the results of the marketing efficiency analysis show that channel 5, namely direct farmers to wholesalers, is the most efficient. Marketing channel 5 consists of 11 farmers with a percentage of 18.3%. The results of the research show that 3 variables influence the choice of marketing channels, namely production volume, farming experience, and education level. Suggestions from research for extension workers and local governments need to assist farmers regarding financing and coffee market information so that marketing channel choices are more varied.